POPULATION PROBLEMS IN KOREA, LOW BIRTH RATE, GENDER EQUALITY AND WOMEN’S SOCIAL STATUS - Dilafruz Sobirova (Ta’lim innovatsiyasi va integratsiyasi, 2024)
Аnnotation. This article describes the structure of government in the Republic of Korea, as well as the division, definition and functions of local government. Population problems, low birth rates, gender equality and the social status of women in Korea were also studied.